The response to hepatitis B vaccine: does it differ in celiac disease? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Objectives There is a relationship between nonresponsiveness to hepatitis B virus (HBV) vaccine and certain human leukocyte antigen (HLA) genotypes. In healthy population, 4-10% vaccine recipients fail to produce protective levels of antibodies to the HBV vaccine after standard immunization depending upon age and the presence of various underlying diseases. Celiac disease (CD) is an HLA-associated immunological disease. It has been suggested that certain HLA haplotypes which are linked to CD are associated with nonresponse to HBV vaccine as well. The aim of this study is to assess the response to HBV vaccine prospectively in a group of CD and to explore the potential link between CD and HBV vaccine nonresponse by studying shared HLA haplotypes. Patients and methods Sixty-three previously diagnosed celiac patients who were on a strict gluten-free diet (GFD) and 54 healthy children were evaluated serologically for anti-HBs status. Celiac children who were anti-HBs negative at baseline were fully vaccinated prospectively, and reevaluated for the response to HBV vaccine. To estimate the role of HLA type in HBV vaccine response in celiac patients, a subgroup of both patients and control participants had HLA genotypes performed. Results At enrollment, 27 (67.5%) children with CD and 48 (85.2%) healthy children were anti-HBs positive, and the difference between patients and controls was statistically significant (P < 0.05). However, failure to respond to HBV vaccine was only 3.6% (response rate 96.4%) in prospectively vaccinated celiac patients. There was no relationship between HLA type and vaccine nonresponse in our study group. Conclusion The response to HBV vaccine in celiac children who were compliant to GFD is not different from a healthy population. CD may be one of the immune diseases associated with a high rate of HBV vaccine nonresponse but it might not be permanent and treatment with GFD and compliance to the treatment may ameliorate the immune response to HBV vaccine in celiac children. Eur J Gastroenterol Hepatol 22:787-793 (C) 2010 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: celiac disease; children; hepatitis B; human leukocyte antigen type; vaccine response; LONG-TERM IMMUNOGENICITY; VIRUS; HLA; NONRESPONSE; EFFICACY; RESPONSIVENESS; PROTECTION; ANTIGEN; BINDING; TRIAL